2018
DOI: 10.1038/s41598-018-25030-6
|View full text |Cite|
|
Sign up to set email alerts
|

Major ocular trauma in Taiwan: 2002–2004 versus 2012–2014

Abstract: We investigated the temporal changes in major eye injuries in Taiwan by reviewing the medical records of all patients with ocular trauma hospitalized at the National Cheng Kung University Hospital during 2002–2004 and 2012–2014. A total of 169 eyes (161 patients) during 2002–2004 and 121 eyes (120 patients) during 2012–2014 were enrolled (mean ± SD age: 41.9 ± 20.8 years in 2002–2004, and 51.8 ± 19.3 years in 2012–2014). Males accounted for ~75% of patients. The most frequent injury-causing object was metallic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
4
3
0
Order By: Relevance
“…Ocular injuries secondary to low falls in this setting increased significantly over the 18-year period from 7.2% to 25.2% and similar trends have been reported in other studies [1,[28][29][30][31]. These injuries are common among older adults however we did not see a clinically meaningful increase in age over the same period, contrary to what has been reported in other literature [28,31]. It may be that any rise in older adults sustaining these injuries in our data was offset by the increase in children suffering NAI.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Ocular injuries secondary to low falls in this setting increased significantly over the 18-year period from 7.2% to 25.2% and similar trends have been reported in other studies [1,[28][29][30][31]. These injuries are common among older adults however we did not see a clinically meaningful increase in age over the same period, contrary to what has been reported in other literature [28,31]. It may be that any rise in older adults sustaining these injuries in our data was offset by the increase in children suffering NAI.…”
Section: Discussionsupporting
confidence: 88%
“…A reduction in RTCrelated injuries may also account for the decline in patients with concomitant facial and pelvic injuries in our cohort as these are commonly associated with this injury mechanism [27]. Ocular injuries secondary to low falls in this setting increased significantly over the 18-year period from 7.2% to 25.2% and similar trends have been reported in other studies [1,[28][29][30][31]. These injuries are common among older adults however we did not see a clinically meaningful increase in age over the same period, contrary to what has been reported in other literature [28,31].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…RTCs, while historically the predominant mechanism, only accounted for 25.3% of cases in 2019/21 and this may account for the reduction in patients with concomitant facial and pelvic injuries in our cohort as these are commonly associated with RTCs 18 . Similar changes in demographics and injury mechanism have also been demonstrated in ocular injury not associated with major trauma in American and Taiwanese populations 19,20 . It has been suggested that older patients are at an increased risk of eye injury due to globe weakness second to previous ocular surgery 21 .…”
Section: Discussionsupporting
confidence: 62%
“…Interestingly the AMPK activator, AICAR impeded LPS- and FA-induced cytokine response, in part through NF-κB inhibition [ 16 ]. However, AICAR has its non-specific limitations, it can inhibit NF-κB DNA binding in human macrophages without AMPK activation [ 66 ].…”
Section: Modulation Of Ampk Activation By Nutrientsmentioning
confidence: 99%